2021
DOI: 10.1016/j.humpath.2020.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in the postmortem liver of patients with coronavirus disease 2019 (COVID-19)

Abstract: Introduction Although COVID-19 is transmitted via respiratory droplets, there are multiple gastrointestinal and hepatic manifestations of the disease, including abnormal liver-associated enzymes. However, there are not many published articles on the pathological findings in the liver of COVID-19 patients. Methods We collected the clinical data from 17 autopsy cases of COVID-19 patients including age, sex, BMI, liver function test (ALT, AST, ALP, direct bilirubin and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 23 publications
2
95
2
6
Order By: Relevance
“…Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) has confirmed the presence of SARS-CoV genome in hepatic tissue, suggesting that COVID-19 may be directly binding to the liver microvasculature and causing hepatic complications ( 73 , 74 ). Post-mortem studies of patients who died following COVID-19 infections demonstrated platelet-fibrin micro-thrombi within the hepatic microvasculature, various degrees of steatosis and portal histiocytic hyperplasia, and hepatic tissue ischemic necrosis ( 75 ). Another study reported patchy necrosis of the liver as well as wide infiltration by small lymphocytes ( 76 ).…”
Section: Organ System Complicationmentioning
confidence: 99%
“…Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) has confirmed the presence of SARS-CoV genome in hepatic tissue, suggesting that COVID-19 may be directly binding to the liver microvasculature and causing hepatic complications ( 73 , 74 ). Post-mortem studies of patients who died following COVID-19 infections demonstrated platelet-fibrin micro-thrombi within the hepatic microvasculature, various degrees of steatosis and portal histiocytic hyperplasia, and hepatic tissue ischemic necrosis ( 75 ). Another study reported patchy necrosis of the liver as well as wide infiltration by small lymphocytes ( 76 ).…”
Section: Organ System Complicationmentioning
confidence: 99%
“…Furthermore, use of liver organoids that have been derived from human pluripotential stem cells are able to support virus replication. 149 A number of autopsy studies detailing the liver pathology in COVID-19 have been reported in the United States, 142,150 Belgium 103,146 and Netherlands, 103 in which a common feature is steatosis (often microvesicular), platelet fibrin microthrombi, lobular inflammation, Zone 3 haemorrhage and ischaemic type hepatic necrosis. The challenge with these finding is that hepatic pathologies such as steatosis can be seen in patients who have a high risk of developing severe disease, that is, diabetes, obesity and patients with cardiovascular disease.…”
Section: Livermentioning
confidence: 99%
“…In some cases, elevated interstitial CD68 + macrophage numbers were reported [ 47 ]. Moreover, patients with COVID-19 showed distinct hepatic symptoms [ 48 ]. Aberrant hepatic enzymes, hyperplasia, platelet-fibrin microthrombi, lobular inflammation, ischaemic hepatic necrosis, and steatosis were observed in the post-mortem livers of patients with COVID-19 [ 48 ].…”
Section: Involvement Of Inflammasomes In Sars-cov-2-derived Organ Damage In Patients With Covid-19 and Comorbiditiesmentioning
confidence: 99%
“…Moreover, patients with COVID-19 showed distinct hepatic symptoms [ 48 ]. Aberrant hepatic enzymes, hyperplasia, platelet-fibrin microthrombi, lobular inflammation, ischaemic hepatic necrosis, and steatosis were observed in the post-mortem livers of patients with COVID-19 [ 48 ]. One of the major causes of death of patients with COVID-19 was respiratory failure [ 49 ].…”
Section: Involvement Of Inflammasomes In Sars-cov-2-derived Organ Damage In Patients With Covid-19 and Comorbiditiesmentioning
confidence: 99%